Diverse Sami Livelihoods: A Comparative Study of Livelihoods in Mountain-Reindeer Husbandry Communities in Swedish Sápmi 1860–1920 - Brännlund, Isabelle (Journal of Northern Studies, 2019)
Swedish state policy regarding the Sami from the late nineteenth century onward and studies on Sami history have tended to treat reindeer husbandry as much more important than other livelihoods practiced by Sami communities and families. By comparing livelihood diversity in southern and northern mountain-reindeer husbandry communities in Swedish Sápmi (the traditional land of the Sami people) during the period 1860–1920, this study challenges the notions of Sami as reindeer herders and mountain reindeer husbandry as a nomadic monoculture. The results shows that Sami communities and families exploited diverse natural resources, trades and means of subsistence. The study supports an understanding of historical Sami livelihoods, were reindeer husbandry as recognized as one of various Sami trades and means of subsistence, rather than as the Sami livelihood.